Pengaruh Kualitas Produk, Kualitas Pelayanan dan Pemesanan Kembali terhadap Kepuasan Konsumen Gerobak Suroboyo - Sefika Mahardian (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine and analyze the influence of product quality, service quality and partial and simultaneous reorders on Suroboyo Gerobak consumer satisfaction. This type of research is research with a quantitative approach. The population in this study were Suroboyo Cart consumers who made purchases more than once, namely 200 consumers. Determining the sample in the study used probability sampling using the Slovin formula so that the number of samples in this study was 100 consumers of Gerobak Suroboyo. The data analysis method in this research uses SPSS analysis tools through validity, reliability, classical assumption tests, namely normality test, multicollinearity test, heteroscedasticity test, multiple linear regression, t test, F test and correlation and determination coefficients. The results of this research show that (1) the product quality variable has no effect on consumer satisfaction, this is proven by the significance value of 0.441 > 0.05. (2) The service quality variable has a significant effect on consumer satisfaction, this is proven by the significance value of 0.026 < 0.05. (3) The reorder variable has a significant effect on consumer satisfaction, this is proven by the significance value of 0.033 < 0.05. (4) Simultaneous test results show that the variables of product quality, service quality and reorders have an influence on Suroboyo Cart consumer satisfaction. This can be proven by the results of Fcount (9.657) > Ftable (2.700) or a significance value < 0.05.